Akal di Tengah Hoaks: Relevansi Mu’tazilah Era Digital - Muhammad Mafaz Kholthy (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the concept of rationality in Mu’tazilah thought, explain its relevance to information-related issues in the digital era, and outline its application in fostering a critical mindset within society. The research employs a qualitative approach, specifically library research utilizing a descriptive-analytical method. Data were gathered from academic books, journal articles, and research findings discussing Mu’tazilah thought, the role of reason, al-uṣūl al-khamsah (the Five Principles), hoaxes, disinformation, digital literacy, tabayyun (verification/clarification), and critical thinking. Data analysis was conducted using qualitative content analysis, involving repeated reading, coding of key ideas, categorization, cross-source comparison, and the interpretation of conceptual relationships. The findings indicate that the Mu’tazilah school positions reason as a crucial instrument for comprehending truth, distinguishing between good and evil, and establishing accountability for human choices. These principles of rationality, freedom, and moral responsibility are relevant in addressing hoaxes, misinformation, disinformation, group fanaticism, social polarization, and the lack of a verification culture in the digital sphere. The values of Mu’tazilah rationality can be actualized through strengthening digital literacy, cultivating the habit of tabayyun, verifying sources, evaluating evidence, engaging in scholarly discussion, and fostering critical thinking education. The study concludes that Mu’tazilah rationality possesses not only historical-theological value but can also be contextualized as an epistemic and ethical foundation for a digital society that is objective, selective, open-minded, and responsible. The implication is that educational institutions can serve as a foundation for developing Islamic Religious Education (PAI) learning based on information verification, argumentative dialogue, and digital communication ethics.